Automatic counter booking system using SMS/ Muhammad Hakim Abdul Wahid & Mohd Fakhruddin Kassim - Abdul Wahid, Muhammad Hakim; Kassim, Mohd Fakhruddin (2015)
The Automatic Counter Booking System using SMS is based on most popular ticketing counter anywhere in the world. Our project will allow users to book in advance the counter-tickets without having to wait in queue. The objective of this project are to design an automatic electronic counter, integrate SMS functions in an electronic counter system, build all in one booking devices and verify the expected result. The problems that lead us in making this project are due to most counter ticketing number devices only allows walk in counter services. Another problem is, the time waiting for someone to be called is long. Lastly is when place is full and dense during peak hour causes discomfort among customer. In our scope of work, we intend to design a device that focus on idea of designing booking system using SMS. We do not want to create a perfect system but rather to make sure that the concept for the book using the SMS contained in our device. Interrupt process is not implemented in this project because it is difficult for us because we do not have enough base for c programming and need more time for us to review how to use the process interrupts . The ways of authentication is by entering a phone number as authentication of users on the system. In this project we used Arduino Mega, SIM900 GSM shield, seven-segment display, Buzzer, Keypad and LCD. To conclude, this project will improve the current counter-ticketing devices and Customers will be able to book in advance their time to visit counter services.